2015
DOI: 10.1186/s40064-015-1191-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in penile cancer: a comparative study between Australia, England and Wales, and the US

Abstract: PurposeTo investigate and compare the trends in incidence and mortality of penile cancer between Australia, England and Wales, and the US, and provide hypotheses for these trends.MethodsCancer registry data from 1982 to 2005 inclusive were obtained from Australia, England and Wales, and the United States. From these data, age-specific, -standardised and mortality:incidence ratios were calculated, and compared.ResultsThe overall incidence of penile cancer in England and Wales (1.44 per 100,000 man-years) was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…A similar pattern has been observed with penile cancer mortality across these three countries . Interestingly, unlike the USA and UK, there is a statistically significant trend towards increasing incidence of penile cancer in Australia .…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…A similar pattern has been observed with penile cancer mortality across these three countries . Interestingly, unlike the USA and UK, there is a statistically significant trend towards increasing incidence of penile cancer in Australia .…”
Section: Introductionsupporting
confidence: 76%
“…In Australia the age-standardised incidence of penile cancer is 0.80/100 000 man years and is lower than the UK (1.44) but higher than the USA (0.66) [6]. A similar pattern has been observed with penile cancer mortality across these three countries [6]. Interestingly, unlike the USA and UK, there is a statistically significant trend towards increasing incidence of penile cancer in Australia [6].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…A 2015 comparative study found that the incidence of penile cancer in the USA is similar to that in Australia, even though circumcision rates in the USA are significantly higher . It has been proposed that the reduced incidence of penile cancer in Australia is associated with the fact that over two‐thirds of older men in Australia are currently circumcised.…”
Section: Circumcision As a Preventative Measurementioning
confidence: 99%
“…10 However, this is not the case in all developed countries, with the incidence being fairly stable over the same time period in the United States. 9 There are several possible causes behind this rise in incidence in England. Infection with human papilloma virus (HPV) is a known risk factor for penile cancer and it is found in about 40%-45% of penile cancers and 80%-100% of cases of PeIN.…”
Section: Discussionmentioning
confidence: 99%